Bioenergy systems for the future : prospects for biofuels and biohydrogen - Dalena, Francesco; Basile, Angelo; Rossi, Claudio (Woodhead Publishing in energy., 2017)
This book examines the current advances in biomass conversion technologies for biofuels and biohydrogen production, including their advantages and challenges for real-world application and industrial-scale implementation.